THE IMPLEMENTATION OF MASLAHAH MURSALAH IN THE CIRCULAR ECONOMY OF WASTE OF UKM TEMPE BERKAH IN HAMPARAN PERAK VILLAGE - Hus Diana; Isnaini Harahap (istinbath, 2023)
This study aims to implement maslahah mursalah in the Circular Economy of UKM Tempe Berkah waste in Hamparan Perak Village by focusing on 3 elements in it, namely hifdzu an-nafs (care of the soul), hifdzu al-mal (maintenance of assets) and hifdzu al-bi'ah (maintenance of environment). This study used a descriptive qualitative research method, with primary and secondary data sources used as data sources. Data collection techniques were used in the form of interviews, observation, and direct surveys. In addition, data collection techniques were also obtained from several selected sources as additional information in this study. The results of the study showed that the implementation of Maslahah Mursalah in the Circular Economy of UKM Tempe Berkah, Hamparan Perak in the element of hifdzu an-nafs (care of the soul) can provide comfort and maintain health for employees, the community, and the surrounding environment from the dangers of pollution. And able to help the community in meeting its basic needs. Then, the implementation of Maslahah Mursalah on the Circular Economy of waste of UKM Tempe Berkah in Hamparan Perak Village in the element of hifdzu al-mal (maintenance of assets), where UKM Tempe Berkah obtains their assets in a good way through buying and selling, using the assets following sharia and there is no element of appropriation other people's assets because they can provide appropriate salaries to their employees so that no one feels abused. And the implementation of Maslahah Mursalah in the Circular Economy of UKM Tempe Berkah's waste in Hamparan Perak Village in the element of hifdzu al-bi'ah (environmental care), namely Tempe Berkah UKM can minimize environmental pollution by managing and utilizing its waste, both solid waste and liquid waste, so as not to cause damage to society and the environment.